PENYULUHAN PENANGANAN BAYI KUNING (IKTERIK) DI DESA LUBUK SUKON KECAMATAN INGIN JAYA KABUPATEN ACEH BESAR - Silvia Yasmin Lubis; Yuli Zuhkrina; Melia Benita; Dewi Hastuti; Nurlaila; Nadila Ayunda; Sri Eva Ridha (Transpublika Publisher, 2020)
The condition of jaundice is very common in newborns, especially in LBW (Low Birth Weight Babies). There are many causes for this yellow baby. What often happens is because the baby's liver function is immature to process erythrocytes (red blood cells). In infants the age of red blood cells is approximately 90 days. The result of the breakdown, erythrocytes must be processed by the baby's liver. At birth the baby's heart is not yet good enough to do its job. The rest of the breakdown of erythrocytes is called bilirubin, this bilirubin is what causes jaundice in babies. Neonatal jaundice is a clinical condition in infants characterized by icterus staining of the skin and sclera due to excessive accumulation of unconjugated bilirubin. Clinical jaundice will begin to appear in newborns when blood bilirubin levels are 5-7 mg/dL. Jaundice during the first week of life is present in about 60% of term infants and 80% of preterm infants. The method used is Pre Test and Post Test using a questionnaire. Based on the results of the counseling there was an increase in respondents' knowledge about handling jaundice (icteric) babies, which were in the good category as much as 47 (88.68%). The conclusion is that there is a significant increase in respondents' knowledge after being given counseling.